2014
DOI: 10.5507/fot.2014.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological characteristics of two ecotypes of Eustigmatos calaminaris sp. nov. (Eustigmatophyceae) inhabiting Zn- and Pb-loaded calamine mine spoils.

Abstract: Knowledge on species diversity and distribution of eustigmatophycean algae (Stramenopiles) in the environment is currently very limited. Some of them are considered promising organisms for industrial application. Phylogenetic analysis of two strains (E120, E5) of a coccoid microalga isolated from highly Zn-and Pb-polluted calamine mine spoils revealed that they belong to the genus Eustigmatos. Cells of both strains were morphologically identical. Some features of their vegetative cells and zoospores differed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Three different techniques were used to stimulate zoospore production. An exponentially growing culture in liquid medium was placed in darkness (wrapped in aluminum foil) for at least 18 h at either 20 °C (lee & Bold 1973) or at 10 °C (Trzcińska et al 2014), or fresh liquid medium was applied to the surface of a culture on agar medium that was over 1 month old which was then placed in darkness for at least 5 days (santos & leedale 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Three different techniques were used to stimulate zoospore production. An exponentially growing culture in liquid medium was placed in darkness (wrapped in aluminum foil) for at least 18 h at either 20 °C (lee & Bold 1973) or at 10 °C (Trzcińska et al 2014), or fresh liquid medium was applied to the surface of a culture on agar medium that was over 1 month old which was then placed in darkness for at least 5 days (santos & leedale 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Since the seminal work of Hibberd (1981), knowledge of eustigmatophyte diversity has expanded with the transfer of additional species from the Xanthophyceae (Schnepf et al 1996;Přibyl et al 2012;Fawley and Fawley 2017) and the descriptions of new taxa (Lubián 1982;Karlson et al 1996;Krienitz et al 2000;Suda et al 2002;Trzcińska et al 2014;Fawley et al 2015), including four new monotypic genera (Preisig and Wilhelm 1989;Neustupa and Němcová 2001;Hegewald et al 2007;Nakayama et al 2015). Recent culture-based and environmental DNA cloning studies have shown that the diversity of the Eustigmatophyceae is much greater than previously expected (Fawley et al 2014).…”
Section: History Of Knowledgementioning
confidence: 99%
“…Less often, eustigmatophytes may be epiphytic (growing on other plants) (Schumacher et al, 1966), epilithic (growing on rocks) (Poulton, 1930), or even as an endosymbiont in the freshwater sponge Corvomeyenia (Frost et al, 1997). Eustigmatophytes may also be common on soils (Hibberd, 1990b;Graham et al, 2009;Trzcyńska et al, 2014).…”
Section: Ecology and Distributionmentioning
confidence: 99%
“…This peculiar feature gives the class its name: Eu = well developed; stigma = eyespot. The latter is a distinct, orange-red extraplastidial eyespot (Trzcyńska et al, 2014).…”
mentioning
confidence: 99%